Language learning through task-based synchronous computer-mediated communication - Suhaila, Mukhtar; Nik Aloesnita, Nik Mohd Alwi; Fatimah, Ali; Nor Shidrah, Mat Daud; Asiah, Kassim; Ainol Haryati, Ibrahim; Nuraihan, Mat Daud (Universiti Malaysia Sarawak, 2024)
A limited number of studies have been conducted on the influence of task features on language production in computer-mediated communication(CMC)environments despite the role of tasks on the language production of L2 students who are mostly non-native speakers (NNSs).Among the prominent hypotheses on the relationship between tasks and language production are the Cognition Hypothesis and the Trade-Off Hypothesis. The current study examined the effect of task structure on student language production in terms of syntactic complexity and fluency in CMC environments. A one-shot design study involved 46 NNS undergraduates in Malaysia and Japan. The respondents were divided into two groups: (1) respondents who performed the task with task structure (+TS) and (2) respondents who performed the task without task structure (-TS). The data were then analysed using a t-test. The present study supported the hypothesis positing that the utilisation of +TS contributes to an increase in syntactic complexity among NNSs, as well as the hypothesis proposing that the use of +TS results in improved fluency. The results also suggest examining additional variables related to task difficulty when designing tasks for CMC environments to assess their effects on fluency and syntactic complexity.